THE PUBLIC RELATIONS GUIDELINE TOWARDS THE DECISION OF STUDENTS AND PARENTS FOR MAKING OF STUDY IN VEERANATSUKSA FOUNDATION SCHOOL PHATTHALUNG DISTRICT PHATTHALUNG PROVINCE - Pengnoo, Tunrada; Sumato, Phamahasupot; Yotarak, Maliwan (Journal of MCU Nakhondhat, 2023)
The objectives of this research are: 1) to study the decision-making conditions of students and parents for study in Veeranatsuksa Foundation School 2) to study the public relations guideline towards the decision of students and parents for making study in Veeranatsuksa Foundation School and 3) to present the public relations guideline towards the decision of students and parents for making of study in Veeranatsuksa Foundation School. This research is qualitative research. The data were collected through in-depth interviews with 15 people. 5 key informants and a focus group of 7 experts. The statistic used content analysis. The results showed that 1. The results of a study on the decision-making conditions of students and parents for choosing Veeranatsuksa Foundation School, there are 7 factors as follows: 1) Vision, image, reputation, administrators, and teachers, including the environment of the school. 2) Social media. 3) Academic factors. 4) Buildings and environmental factors. 5) Teachers and administrators’ characteristics factors. 6) School-community relationship. 7) Family economics. 2. The result of the public relation guideline towards the decision of students and parents for making of study in Veeranatsuksa Foundation school, there are 4 processes by bringing data from all 7 factors based on John E. Marston’s public relations process principal R A C E. Process 1 Research or study of collecting information necessary for public relations. Process 2 Planning and Determining public relations activities. Process 3 Communication for public relations and Process 4 Performance Evaluation. 3. The experts verified the public relation guideline regardings the decision of students and parents for making of study in Veeranatsuksa foundation school and found that regarding the focus group discussion, the guidelines have suitable, possibility and usefulness which can be applicable.